Patient and public involvement in preclinical and medical research: Evaluation of an established programme in a Discovery‐Based Medical Research Institute - Robyn A. Smith; Judith Slocombe; Jo Cockwill; Kathy Minas; George Kiossoglou; Katya Gray; William Lawrence; Michelle Iddles; Clare Scott; Lorraine A. O'Reilly (Health Expectations)
Abstract Background and Context Involving people with lived experience of health conditions and the public (consumers) in health research is supported by policy, practice and research funding schemes. However, consumer involvement programmes in discovery‐based preclinical research settings are uncommon. Few formal evaluations of these programmes are reported in the literature. Objective This study aimed to evaluate an established patient and public involvement programme operating in a major Australian Discovery‐Based Medical Research Institute (DBMRI) to inform programme development and the wider field. Design and Participants A multimethods programme evaluation incorporating demographic, descriptive and qualitative data obtained through consumer/researcher co‐developed online surveys and semistructured virtual interviews. Programme participants (n = 111) were invited to complete an online survey seeking feedback on their experience of involvement, programme processes and perceived impacts. A purposive sample of 25 participants was interviewed. Descriptive data were analysed using explanatory statistics and qualitative data from surveys and interviews were thematically analysed. Results This consumer involvement programme was found to be useful and meaningful for most participants, with specific examples of perceived added value. Consumers most commonly engaged with researchers to inform research development, prepare funding applications or strengthen lay communication of science. Genuine consumer–researcher interactions, relationship development and mutual respect were key elements in a positive experience for participants. Opportunities to ‘give back’, to learn and to ground research in lived experience were identified programme strengths and benefits. Developing researcher training in how to work with consumers, increasing the diversity of the consumer group membership and expanding the range of consumer activities were identified opportunities for improvement. Organisational support and adequate programme resourcing were identified as key enablers. Conclusion Discovery‐based preclinical research is often viewed as being distant from clinical application; therefore, consumer involvement may be considered less relevant. However this study identified value in bringing a strong consumer voice to the discovery‐based research process through a coordinated, organisation‐wide approach with the potential for application in similar preclinical research settings. Patient or Public Contribution Four consumer partners from the DBMRI Consumer Advisory Panel were actively engaged in developing this programme evaluation. Specifically, these consumer partners co‐developed and pilot‐tested surveys and interview guides, reviewed and commented on project data analysis and reporting and also contributed as co‐authors by editing the manuscript.